E-inclusion technologies for the speech handicapped (2008)
This paper addresses the problem that disabled people face when accessing the new systems and technologies that are available nowadays. The use of speech technologies, specially helpful for motor handicapped people, becomes unapproachable when these people also suffer speech impairments, making the gap in the society wider for them. As a way to include speech impaired people in the technological society of today, two lines of work have been carried out. On one hand, a computer-aided speech therapy software has been developed for the speech training of children with different disabilities. This tool, available for free distribution, makes use of different state-of-the-art speech technologies to train different levels of the language. As a result of this work, the software is being used currently in several centers for special education with a very encouraging feedback about the capabilities of the system. On the other hand, research on the use of automatic speech recognition (ASR) systems for the speech impaired has been carried out. This work has focused on current techniques of speaker adaptation to know how these techniques, fruitfully used in other tasks, can deal with this specific kind of speech. The use of Maximum A Posterior (MAP) obtains an improvement of 60.61% compared to the results of a baseline speaker independent model.